The effects of integration agreements in Western Hemisphere trade, 1970–2014. Issue 5 (3rd July 2016) - Martin-Mayoral, Fernando; Morán Carofilis, Gabriela; Cajas Guijarro, John
Abstract : The paper analyzes the effects of four regional integration agreements (Common Market of the South [MERCOSUR], Andean Community [ANCOM], Central American Common Market [CACM] and North America Free Trade Agreement [NAFTA]) on bilateral trade in 19 countries from the Western Hemisphere for the period 1970–2014. For this purpose we estimate different gravity models to control for trade creation and diversion, export diversification and intra-industry trade using OLS log-linearized gravity model and Poisson pseudo-maximum-likelihood panel data estimators that allow controlling for zero-value trade flows. We find trade creation for ANCOM, MERCOSUR and CACM and trade diversion for NAFTA and MERCOSUR countries. Export diversification negatively affects bilateral trade in all American agreements, while intra-industry trade has contributed to trade expansion in ANCOM and the opposite for NAFTA, MERCOSUR and CACM. Global supply chains may help us explain these results. Finally, we find anticipatory effects on trade several years before the signing of the agreements, but only NAFTA countries seem to be natural trading partners in the region while the rest of Latin American regional agreements have not resulted in a comprehensive, profound and consolidated common market.